Bancah: Local Knowledge, Cultural Adaptation, and its Challenges - Delfi, Maskota; Arifin, Zainal; Pujiraharjo, Sidarta; Jelly, Jelly; Irwandi, Ade (Humaniora: Journal of Indonesia Culture and Society, 2025)
The research explains the concept of bancah, which translates to "swamps," as a source of ecological wisdom and an integral part of Minangkabau local knowledge. In Minangkabau society, bancah has traditionally been vital to the community's social and cultural life. While many people today view bancah as unproductive, their ecological and cultural significance is deeply rooted in Minangkabau identity. The research employs an ethnoscience approach, complemented by methods such as interviews, field observations, and literature reviews, to explore local memories and knowledge about bancah in the Minangkabau community, particularly in the Kuranji and Nanggalo districts of Padang. The analysis focuses on how the community understands bancah and its meanings to ecology and culture. The findings show that bancah traditionally teaches respect for nature and acts as an informal educational resource that promotes sustainable practices. However, changes in land use and modern economic needs have led younger people to view bancah mainly as a source of income, overlooking its ecological and cultural importance. This shift poses a threat to the preservation of traditional knowledge and disrupts the ecological connections that are vital to Minangkabau cultural identity. The transformation of bancah reflects a larger shift in collective memory and cultural values, indicating the weakening bond between the Minangkabau community and its wetland heritage due to urban development. Preserving bancah as an ecological and cultural resource is crucial for maintaining local food security (sago), ensuring environmental stability, and preserving the connection of the Minangkabau people with their cultural heritage.